RECRUTAREA ŞI SELECTAREA CADRELOR DIDACTICE - FUNCŢIE CENTRALĂ A MANAGEMENTULUI RESURSELOR UMANE ÎN ÎNVĂŢĂMÂNT - USM ADMIN (Moldova State University, 2011)
The present article addresses the problem of teacher recruitment and selection as a function of human resource management. The content is relevant to management experience and offers a variety of methods, recruitment, methods of selection of teachers and a number of documents related to these processes.